Pore Pressure Estimation Using Bowers Methods in Shale Gas Reservoir Jambi Sub-Basin - Benny A. Bungasulu (Jurnal Fisika Papua, 2022)
Pore pressure prediction has important implications in determining the success of a drilling activity. Information of subsurface pore pressure prediction in hydrocarbon exploration and production is very important. For geologist this information can be used to determine of hydrocarbon generation and maturation within a basin, while for petroleum engineer pore pressure prediction is very important to maintain the production rate and for drilling engineer this information is useful for mud weigh and casing designs prior drilling activities to prevent blow out. This study is conducted in the well A and B, Field "X", Jambi Sub-Basin. Wells A and B have problems when drilling operations are carried out, such as blow out and pipe sticking which causes high non-productive time (NPT). So, optimum pore pressure prediction analysis must be carried out to avoid downhole problems in the implementation of further development well drilling. First, this study identifies the mechanism of overpressure formation, then predicts pore pressure using the Bowers method and subsequently performs modeling of subsurface 3D pore pressure. The results of the analysis showed that overpressure occurred in the Gumai and Talang Akar Formations, overpressure mechanism in the formation was caused by compaction, fluid expansion (kerogen maturation), and based on analysis of 3D pore pressure modeling many overpressure zones were found in the Gumai Formation, Jambi Sub-Basin